Strengthening the resilience of aquaculture competitiveness in EU economies: an empirical analysis - Alsaleh, Mohd; Abdul-Rahim, A. S. (Israeli Journal of Aquaculture - Bamidgeh, 2025)
The European Union (EU27) faces significant challenges in enhancing the global competitiveness of its aquaculture market, such as stagnant production, high production costs, competition from cheaper imports, focus on sustainability, and consumer preferences. Thus, the main goal of this research is to explore how factors related to global competitiveness influenced the growth of the aquaculture sector in the EU27 from 1990 to 2023. The methods of ordinary least squares (OLS), two-stage least squares (2SLS), and robust least squares (RLS) estimations were used to address the endogeneity problem to arrive at the most important results. The effect sizes indicate that the system of innovation and human capital have a greater influence on the development of the aquaculture sector in the highly developed EU14 countries compared to the developing EU13 nations. The exact outcomes of the applied methods, however, demonstrate that the aquaculture market’s expansion in EU13 developing nations is more influenced by market size, institutional quality, and economic growth compared to EU14 members. This study recommends that the EU27 region emphasize policy adjustments to balance sustainability with competitiveness, which includes streamlining regulations, improving access to financing, and fostering innovation in aquaculture technologies.